Konstruksi Gender dalam Novel Geni Jora Karya Abidah El-Khalieqy - . Wiyatmi (Humaniora, 2010)
Who was the woman? This question was a basic question that tried to understand who, how, and where the woman was positioned in his community. The Geni Jora novel by Abidah El-Khalieqy was a novel that tried to question this matter. In this novel was expressed by the gender construction that had a background the Islam religion that placed the woman as the second class tha always must yield so that the available life order could go well. By using the perspective of Islam feminism, was expressed that the construction gender this was no in accordance with the spirit of the Islam religion (Al-Qur'an) tha stressed justice and equality gender. Therefore, the construction gender this was opposed by the Kejora leading figure with always evaluated and showed his achievement so as to be able to achieve gender equality.